Prognostic Impact of Metabolism Reprogramming Markers Acetyl-CoA Synthetase 2 Phosphorylation and Ketohexokinase-A Expression in Non-Small-Cell Lung Carcinoma - Yang, Xueying; Shao, Fei; Shi, Susheng; Feng, Xiaoli; Wang, Wei; Wang, Yalong; Guo, Wei; Wang, Juhong; Gao, Shugeng; Gao, Yibo; Lu, Zhimin; He, Jie (Frontiers in Oncology, 2019)
Background. The identification of prognostic markers for non-small-cell lung carcinoma (NSCLC) is needed for clinical practice. The metabolism-reprogramming marker ketohexokinase (KHK)-A and acetyl-CoA synthetase 2 (ACSS2) phosphorylation at S659 (ACSS2 pS659) play important roles in tumorigenesis and tumor development. However, the clinical significance of KHK-A and ACSS2 pS659 in NSCLC is largely unknown. Methods. The expression levels of KHK-A and ACSS2 pS659 were assessed by immunohistochemistry analyses of surgical specimens from 303 NSCLC patients. The prognostic values of KHK-A and ACSS2 pS659 were evaluated by Kaplan-Meier methods and Cox regression models. Results. The expression levels of KHK-A and ACSS2 pS659 were significantly higher in NSCLC tissues than those in adjacent non-tumor tissues (P<0.0001). KHK-A or ACSS2 pS659 alone and the combination of KHK-A and ACSS2 pS659 were inversely correlated with overall survival in NSCLC patients (P<0.001). The multivariate analysis indicated that KHK-A or ACSS2 pS659 and KHK-A/ACSS2 pS659 were independent prognostic biomarkers for NSCLC (P=0.008 for KHK-A, P<0.001 for ACSS2 pS659, and P<0.001 for KHK-A/ACSS2 pS659). Furthermore, the combination of KHK-A and ACSS2 pS659 can be used as a prognostic indicator for all stages of NSCLC. Conclusions. KHK-A or ACSS2 pS659 alone and the combination of KHK-A and ACSS2 pS659 can be used as prognostic markers for NSCLC. Our findings highlight the important role of metabolic reprogramming in NSCLC progression.